Association of GRACE Risk Score with Angiographic Severity of Coronary Artery Disease in patients with ST Elevation Myocardial Infarction (Cardiovascular Journal, 2015)
Background: Clinical guidelines recommend that optimal management of acute coronary syndrome should include patient risk stratification. Predicting the anatomical extension of coronary artery disease is also potentially useful for clinical decision. The objective of our study is to determine whether the GRACE risk score correlates with the angiographic extent and severity of coronary artery disease in patients with ST elevation myocardial infarction.Methodology: 50 patients diagnosed with Acute Myocardial Infarction were included as sample by purposive sampling method. GRACE risk score for each patient was calculated and the patients were divided into groups according to the GRACE risk score: low risk (